Worldview from Balinese Suicide Notes: A Cultural Forensic Linguistic Perspective - Putu Wahyu Widiatmika; I Wayan Pastika; Christopher Kinipi (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
Bali, which has the highest suicide rate in Indonesia, provides a critical context for examining suicide notes as both cultural texts and forensic evidence. This study examines how Balinese people communicate finality through language and how these styles relate to authenticity. Five suicide notes, written in Balinese and verified by authorities as genuine, were purposively sampled from online news. Using qualitative content analysis within frameworks of Olsson’s Insider and Outsider and Cultural Discourse Analysis, the findings show that authenticity is conveyed indirectly through culturally disciplined language rather than explicit declarations. Finality is predominantly framed through a journey metaphor which reflects Balinese Hindu beliefs. This study contributes to forensic linguistics by demonstrating that authenticity in local suicide notes is inseparable from local cultures and norms.